The TRIPS waiver proposal: an urgent measure to expand access to the COVID-19 vaccines - Menezes, Henrique Zeferino de (South Centre, 2021)
Despite multilateral commitments and political statements of solidarity and cooperation to guarantee the availability and access to COVID-19 vaccines (and other relevant technologies for control and treatment), the scenario after the beginning of vaccination is marked by the deepening of vaccine nationalism, the concentration of inputs and vaccines production, and the uneven distribution of options of vaccine doses already approved for use. This pattern of production restrictions and unequal access will lead to an increase in international inequalities, leaving a large part of the world to have access to vaccines not until 2024. While advanced purchase agreements (APAs) among pharmaceutical companies and some developed countries are multiplying, the proposed mechanisms for voluntary licensing of technologies and the COVAX Facility do not achieve their goal of democratizing access to vaccines. In this sense, the current TRIPS (Agreement on Trade-Related Aspects of Intellectual Property Rights) waiver proposal seems to be the political and institutional response with the greatest potential to guarantee the scaling of the production of pharmaceutical inputs, allowing the adoption of a comprehensive strategy to ensure timely, sufficient, and affordable access to all technologies developed to fight COVID-19.
10419/248628
Keywords: Graue Literatur; Access to COVID-19 Tools (Accelerator) - (ACT); Access to Medicines; Advanced Purchase Agreements (APAs); Big Pharma; Coronavirus; COVAX Facility; COVID-19; Diagnostics; Global Health; Health; Health Technologies; India; Innovation; Intellectual Property; Medical Technology; Pandemic; Public Health; Research and Development (R&D); South Africa; South-South Cooperation; TRIPS; TRIPS Council; TRIPS Waiver; United Nations (UN); United Nations General Assembly (UNGA); Vaccine Nationalism; Vaccines; World Health Assembly (WHA); World Health Organization (WHO); World Intellectual Property Organization (WIPO); World Trade Organization (WTO)